FILSAFAT IKHWAN ASH-SHAFA - Hady, M. Samsul (ULUL ALBAB Jurnal Studi Islam, 2007)
Brethren of Purity (Ikhwan al-Safa) is a group of philosophers in medieval Islamic history. They declared themselves as opponents of any chastity, impurity, or opacity. Their thoughts compiled in an encyclopedia containing of fifty two treaties (epistles), titled al-Rasa'il Ikhwan al-Safa wa Khullan al-Wafa. Al-Rasa'il extensively surveys a huge range of subjects ranging from music to magic. They are didactic in tone and highly eclectic in content, providing both pedagogical and culture mirror of their Age and its diverse philosophies and creeds. Therefore, al-Rasail is still debatable of its origin, one claims to the writing of Ali bin Abi Talib, the fourth Muslim Caliph (d. 40/661), or the writing of the sixth Shi'ite imam, Imam Ja'far al-Sadiq. The encyclopedia aspires to encompass all knowledge, from all sources, and to give meaning to the struggles of the human race. One of all amazing notions of the Brethren of Purity is a numerical symbolism as applied to explain qualitative correspondence of three principal beings: God as The Creator, universe, and human being.